Kontribusi Sikap Pada Mata Kuliah Pengantar Akuntansi, Konsep Diri dan Kualitas Pembelajaran Terhadap Prestasi Belajar Mata Kuliah Pengantar Akuntansi Pada Mahasiswa Semester II Fakultas Ekonomi Universitas Megoupak Tulang Bawang Tahun 2013 - 2014 - Arni, Yusni (Lentera: Jurnal Ilmiah Kependidikan, 2017)
One indicator of the student progress in the teaching â learning process is the students improvement at every evaluation. If the score is low, it means that the students is not successful in his her learning. Presurvey result in faculty of economics in the University of Megoupak Tulang Bawang indicated that the students score mostly C, this caused by several factors influencing the students achievement learning .This research is objected to identify the relationship of (1) students attitude in the accounting introductory subject and the learning achievement (2) self concept and learning achievement (3) learning quality and the learning achievement, and (4) students attitude at accounting introductory, self concept, and learning quality and learning achievement. The research used survey method that is, studying large and small population by selecting and studying the chosen sample of the population in order to find insidence, distribution, and relative interrelationfrom the sociological and psychological . Based on the result of the analysis and discussion, it can be concluded that (1) there was a relationship betweenstudents attitude in the accounting introductory subject gave contribution 15,8% towards the students achievement in learning (2) there was a relationship between self concept and learning achievement. Self concept gave contribution 18,3% towards the student achievement in learning (3) there was a relationship between learning quality and learning achievement. Learning quality gave contribution 9,5% towards the student achievement in learning (4) There was a relationship among students attitude at accounting introductory, self concept, learning quality and learning achievement gave contribution 29,3% towards student learning achievement.